Reconstructionism Philosophy Perspective in Developing Curriculum - Nugroho, Listyanto Aji (HISTORIKA, 2020)
Philosophy of education is an essential need to become an ideological framework and reference to carry on the process of education. In the field of curriculum, philosophy is determining goals, content, implementation guideline, and evaluation. There are many kinds of philosophies on education: perennials, essentialism, progressivism, Reconstructionism. This paper aimed to study Reconstructionism philosophy and how this perspective is used to construct a curriculum. This paradigm persuades us to radically reform the educational system and curriculum and make a new social order to a better world with more sensitivity to update issues and social problems that occur. The main issue is equality in education. Curriculum with reconstructionism paradigms persuades students and teachers to become agents of social change. Reconstructionism is giving birth to globalism and reconceptualize the way of thinking.